2013
DOI: 10.1371/journal.pone.0065450
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Functional Regulation of Melanocortin 2 Receptor (MC2R) in the Sea Bass. A Putative Role in the Adaptation to Stress

Abstract: The activation of melanocortin 2 receptor (MC2R) by ACTH mediates the signaling cascade leading to steroid synthesis in the interrenal tissue (analogous to the adrenal cortex in mammals) of fish. However, little is known about the functional regulation of this receptor in fish. In this work described, we cloned sea bass MC2R from a liver cDNA. SbMC2R requires the melanocortin 2 receptor accessory protein (MRAP) for its functional expression. Dietary cortisol but not long-term stress protocols downregulated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 45 publications
(71 reference statements)
2
39
0
Order By: Relevance
“…; Agulleiro et al . ). ESR2 belongs to the nuclear receptor family of transcription factors involved in the regulation of spermatogenesis.…”
Section: Resultsmentioning
confidence: 97%
“…; Agulleiro et al . ). ESR2 belongs to the nuclear receptor family of transcription factors involved in the regulation of spermatogenesis.…”
Section: Resultsmentioning
confidence: 97%
“…mc2r is a member of melanocortin receptor family, expressed in interrenal cells at high levels and detectable in adipose tissue . mc2r gene products specifically bind to ACTH while other melanocortin receptor members (eg, mc1r, mc3r ‐ mc5r ) bind to melanocyte stimulating hormone as well as ACTH . mc2r initiates corticosteroid synthesis by increasing cyclic adenosine monophosphate (cAMP) levels, which in turn increases free cholesterol levels available for mitochondrial transport where corticosteroid synthesis occurs .…”
Section: Discussionmentioning
confidence: 99%
“…mc2r has two exons and only exon 2 is protein coding. The Mc2r protein is a trans‐membrane protein with only one known transcript and translational isoform . In contrast, NR3C1 in humans has eight translated exons (exon 2 through 9) and nine untranslated alternative first exons, each with a different promoter.…”
Section: Discussionmentioning
confidence: 99%
“…whereas the reference genes eukaryotic elongation factor 1 ( elf1a ) and ribosomal 18S RNA ( 18S ) were used as in previous work41. Primer design for melanocortin 1 receptor ( mc1r ), melanocortin 2 receptor ( mc2r ) and pro-opiomelanocortin ( pomc ) was based on the available sequences with accession numbers FN377856.142, FR870225.114, and AY691808.14. The forward primer for mc1r has the sequence 5′ CTCCACCTCATCCTCATC 3′ while the reverse 5′ GAAGCACCAAGAACACAG 3′.…”
Section: Methodsmentioning
confidence: 99%
“…Relatively few studies have focused on the function and characterization of MC2R in fish910111213 and a recent study conducted in European sea bass demonstrated a negative feedback by cortisol on MC2R expression in a chronic stress paradigm14.…”
mentioning
confidence: 99%